Qualidade informacional em padrão contábil societário e em padrão contábil regulatório: evidências no setor de energia elétrica - Morais, Cinthya Rachel Firmino de (2019)
The Brazilian process of convergence to International Financial Reporting Standards (IFRS), with Law No. 11,638/07, directed significant changes in accounting regulation, moving from explicit rules paradigm to standards focused on principles; application of preparers’ discretionary decisions and alignment to supply useful information for investors’ economic decision making. This new accounting standard was not fully accepted, with regulatory agencies adopting differentiated solutions to disclosure accounting information by firms under its support, arguing different users’ demand for accounting information, which quality requirements should be related with political and institutional national environment . The research focuses on ANEEL Normative Resolution No. 396/2010, which established a regulatory accounting standard, in parallel with corporate accounting standard (IFRS) for electric sector firms, publishing both simultaneously, to compare the level of accounting information quality in reported statements prepared under both accounting standards (corporate and regulatory), given regulators intention to meet different external users’ demand. Publicly traded electric industry companies operating in Brazil and listed in Brasil Bolsa Balcão (B3) were sampled covering 2011 to 2017 period; 29 company’s financial statements data in both standards, corresponding to 203 doubled observations-year were investigated. Informational quality formulations of conditional conservatism; unconditional conservatism; income smoothing; and value-relevance were tested. Findings indicated no evidence or differentiation regarding conditional conservatism among different accounting standards; furthermore, persistence bias for unconditional conservatism was observed on corporate standards, while regulatory accounting system just fully incorporates the firm's economic value; smoothing measures are more critical in regulatory standard statements, when compared to corporate standard numbers; accounting earnings and equity published by corporate standard model are more value-relevant; to a lesser extent, only equity is value-relevant in regulatory accounting way. Additionally, IFRS standard earnings are consistently higher than those reported in regulatory standard; these differences are not showed up in equity values, leading to infer that earnings differences are adjusted temporally. It’s worthing to highlight that matching provided diverse amounts on accounting information referring to the same economic reality.